2015
DOI: 10.1063/1.4907534
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced charge recombination due to surfaces and twin defects in GaAs nanostructures

Abstract: Power conversion efficiency of gallium arsenide (GaAs) nanowire (NW) solar cells is severely limited by enhanced charge recombination (CR) at sidewall surfaces, but its atomistic mechanisms are not well understood. In addition, GaAs NWs usually contain a high density of twin defects that form a twin superlattice, but its effects on CR dynamics are largely unknown. Here, quantum molecular dynamics (QMD) simulations reveal the existence of an intrinsic type-II heterostructure at the (110) GaAs surface. Nonadiaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Compared with thin film-based photodetectors, GaAs NWs-based photodetectors provide higher light sensitivity and internal photoconductivity gain because of their large surface-to-volume ratio and low area fill factor [14,15]. However, reports on the photoconductance properties of GaAs NWs are still lacking, most likely due to the large density of surface states, which tends to degrade device characteristics by pinning the surface Fermi energy [17][18][19][20]. Usually, an AlGaAs shell layer has been grown on the surface of the GaAs NWs to passivate the core surface effectively [14,16,21,22].…”
Section: Introductionmentioning
confidence: 98%
“…Compared with thin film-based photodetectors, GaAs NWs-based photodetectors provide higher light sensitivity and internal photoconductivity gain because of their large surface-to-volume ratio and low area fill factor [14,15]. However, reports on the photoconductance properties of GaAs NWs are still lacking, most likely due to the large density of surface states, which tends to degrade device characteristics by pinning the surface Fermi energy [17][18][19][20]. Usually, an AlGaAs shell layer has been grown on the surface of the GaAs NWs to passivate the core surface effectively [14,16,21,22].…”
Section: Introductionmentioning
confidence: 98%
“…some excitons 22 and reduce charge carrier mobilities 23 . It has been proposed that they are responsible for enhanced recombination at the NW surfaces 24 , although surface recombination is a well-known problem that is addressed by core-shell structures to confine carriers to the NW core. 17…”
mentioning
confidence: 99%
“…Additionally, the presence of twin domains in tetragonal MAPbI 3 was discussed by Rothmann et al and is shown in figure 4(f) [84]. Twin boundaries impact charge separation, transport, and recombination [96]. The width of the twin domains present in MAPbI 3 films range from 100 to 300 nm and their formation/disappearance is reversible when transitioning through the cubic/tetragonal phase change [84].…”
Section: Nanoscale Absorber Level Characterizationmentioning
confidence: 85%
“…At the same time, a key goal is to characterize how perovskites transform in the presence of electric fields and illumination. Thus, in situ tracking of the evolution of perovskites in active devices represents a challenge but has been demonstrated recently employing interdigitated back-contacted substrates [96].…”
Section: Discussion and Outlookmentioning
confidence: 99%